Leapfrogging Towards a Sustainable Dairy Breeding Program in Tanzania - Msuta, G.; Lyatuu, Eliamoni T.R.; Kelya, Neema; Komwihangilo, Daniel M.; Gebreyohanes, Gebregziabher; Ojango, Julie M.K.; Kahumbu, S.; Chinyere, Ekine; Mrode, Raphael A.; Okeyo Mwai, Ally (2023)
Tanzania smallholder dairy is constrained by lack of access to high yielding and locally adapted genetics. To improved dairy genetics Artificial insemination (AI) is the best tool to use. However, uptake of AI services is variable across the country. Information on individual animals born through AI and their performance levels within the different environments are lacking, hence difficult to evaluate the performance of the progeny born from AI bulls and to select best genetics. To develop a successful breeding program, regular animal performance recording is necessary that will provide reliable records for genetic evaluation and ranking of animals based on the performance in different traits of choice to be used as parents of future replacement in the herd. The African Asian Dairy Genetic Gains (AADGG) program in partnership with the International Livestock Research Institute (ILRI) and Tanzania Livestock Research Institute (TALIRI) initiated a national dairy performance recording, evaluation, and breeding program in 2016. This paper reports on the journey so far in building a breeding program at the national level and suggests a way forward for its sustainability. The program started with revamping the existing national animal identification system. This involved initiating farmer, herd, and individual animal registration, establishing a national digital database that enabled recording and genotyping of cows and bulls owned by farmers. From 2016 to 2023, 33,769 farms with 79,269 animals have been registered, and total of 260,827 test-day milk yields and 44,853 body weight records have been captured. About 7,458 animals have been genotyped and used to generate genomic breeding values. Results from the genomic evaluations were used to develop a selection index that improves the rate of milk production but keeps the body weight constant. Semen from the top bulls is being produced and promoted through AI to benefit thousands of dairy farmers. From the analysis of the production trends, an improvement of approximately 54% (from an average of 6.7 litres to 10.34) of milk yield/cow/day, from 2016 to-date is reported. Therefore, the Tanzanian dairy industry can benefit from sustained breeding program that continuously identifies and delivers improved adapted and productive dairy genetics.